Global civics responsibilities and rights in an interdependent world - Hakan, Altinay (Washington, D.C Brookings Institution Press, 2011)
The simple yet challenging goal of this book is to deliberate the legitimacy, and advance the feasibility, of an important new concept ?the notion of "global civics." We cannot achieve the international cooperation that is needed for a globalizing and interdependent century without embracing and implementing this important concept.
Includes bibliographical references and index.
Keywords: World citizenship